Library Handbook for Organic Chemists - David Flaxbart (Issues in Science and Technology Librarianship)
The article reviews the book Library Handbook for Organic Chemists. NY: Chemical Publishing Co., 2000. ISBN 0-82060-361-9. $64.95 (paper) by Andrew J. Poss.